Local Community Involvement: A Case of REDD+ Program Indonesia’s - Md. Ashrafuzzaman; Md. Sayedur Rahman (Budapest International Research and Critics University, 2020)
Over the past 30 years, environmental aspects have had a wide-ranging influence on development policy and overall guidance. Climate change points out the limitations of nation-state border construction, especially where international cooperation is needed. The concept of ecological imperialism requires high-income countries to exert pressure on low- and middle-income countries in order to realize the environmental protection agenda. The pressure of international organizations to use aid and loan conditions to protect forests is an example. From a global perspective, the author also focuses on the state level. Even if the affiliation with the regional environment is restricted, the government's deforestation agreement can be coordinated with international climate treaties. However, there is no internationally binding agreement on deforestation with Indonesia, partly because of the country’s economic interests in the logging industry, so the government claims the sovereignty of national forest management. Therefore, deforestation advocates are required to find other channels to influence environmental deprivation. This article will study this expression of inclusion, and by applying Lee’s observations on the subject, to what extent. In this research, the concepts of